Produksi Benih Cabai Rawit (Capsicum frutescens L.) Bebas TMV(Tobacco mosaic virus) Melalui Dry Heat Treatment - I KETUT SIADI; I GUSTI NGURAH RAKA; I GUSTI NGURAH WISNU PURWADI (Agrotrop : Journal on Agriculture Science, 2012)
The study was done in Denpasar, Bali under greenhouse condition as well as in the field. The objective of the research is to know the effectiveness of dry heat treatment to inactivate TMV which was contaminated chili pepper seeds, and to improves the seeds quality. The seeds which were dry heated under 40ºC for 24 hours and hereinafter 70ºC for 72 hours showed to have no different viability with those of non treated seeds. These indicated that dry heat treatment does not affect to germination of chili pepper seeds. The dry heat treated chili pepper seeds (DHS), non treated ones (NT), and manually TMV-contaminated DHS (DHS+TMV) were planted under field condition. Verification of TMV infection in the 90 days old chili pepper plants by enzyme-linked immunoassay revealed that the rate of TMV infection were 57.89%, 12.5% and 100% for NT, DHS and DHS+TMV. These results indicated that the TMV source was abundance in the field. Infection of TMV in the chili pepper plants given much effect on the plant height, branch number and production. These research results suggest a possibility of using dry heat.